Developing a student well-being model for schools in Pakistan. (March 2019) - Zulfiqar, Asma; Syed, Faiza Rahman; Latif, Fatima Farida
This article aims to explore the concept of student well-being and how it can be introduced and integrated within Pakistan's educational structure. The basis of the discussion is built around the need for having a student well-being model for schools in Pakistan. For the purpose of the study, the information is gathered inductively through a detailed literature review of the relevant data, which was further supplemented by three case studies from the public, private and catholic schools in Victoria, Australia. Along with this, extensive literature review was made of Pakistan's education system. Following the completion of the literature review and case studies, a comprehensive framework is proposed along with a student well-being management plan for developing and integrating the student well-being model into the existing educational programme in the country.